2019
DOI: 10.3390/jcm8040537
|View full text |Cite
|
Sign up to set email alerts
|

T-Regulatory Cells Confer Increased Myelination and Stem Cell Activity after Stroke-Induced White Matter Injury

Abstract: Stroke-induced hypoxia causes oligodendrocyte death due to inflammation, lack of oxygen and exacerbation of cell death. Bone marrow-derived stem cells (BMSCs) possess an endogenous population of T-regulatory cells (Tregs) which reduce secretion of pro-inflammatory cytokines that lead to secondary cell death. Here, we hypothesize that oligodendrocyte progenitor cells (OPCs) cultured with BMSCs containing their native Treg population show greater cell viability, less pro-inflammatory cytokine secretion and great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…It has been demonstrated that the development of GMH leads to inflammation damaging the periventricular white matter, apoptosis and arresting maturation of oligodendrocyte precursor cells, and hypomyelination 47 . Negative effects of inflammation, resulting in the white matter loss have been observed in both preclinical and clinical studies [48][49][50] . Infants suffering GMH are prone to disrupted white matter www.nature.com/scientificreports www.nature.com/scientificreports/ maturation and impaired cognitive development 51 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the development of GMH leads to inflammation damaging the periventricular white matter, apoptosis and arresting maturation of oligodendrocyte precursor cells, and hypomyelination 47 . Negative effects of inflammation, resulting in the white matter loss have been observed in both preclinical and clinical studies [48][49][50] . Infants suffering GMH are prone to disrupted white matter www.nature.com/scientificreports www.nature.com/scientificreports/ maturation and impaired cognitive development 51 .…”
Section: Discussionmentioning
confidence: 99%
“…NCS‐01 cells' ability to interact with the microenvironment niche, via the cells' filopodia formation, may allow a reciprocal and regulated modulation of the cytokine secretion toward neuroregeneration. Finally, although solid safety record of MSCs is documented in hematological indications, additional studies may be warranted to address the cells' high proliferative capacity . Notwithstanding these scientific limitations, these translational studies formed the key material of an IND package that was deemed by the FDA as sufficient to grant approval in July 2019 to proceed with the clinical trial of NCS‐01 cells in ischemic stroke patients.…”
Section: Discussionmentioning
confidence: 99%
“…48,49 The only FDA-approved drug is tPA with limited treatment window and high risk of hemorrhagic transformation; hence, there is a significant need for finding a novel treatment for stroke. Recently, stem cell therapy has emerged as a promising experimental treatment, even reaching clinical trials, for neurological diseases, including stroke, 49,50 possibly due to the grafted cells' bystander effects such as secretion of growth factors and cytokines associated with neurogenesis, angiogenesis, vasculogenesis, and mitochondrial repair. 48,49,51,52 Here, we demonstrated the appealing therapeutic properties of NCS-01 cells, namely cell secretion of bFGF and IL-6, and filopodia extension in rescuing ischemic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Behm, C. et al observed that Vitamin D3 increases or decreases the immunomodulatory activities of Periodontal ligament-MSCs, depending qualitatively and quantitatively on the presence of specific tumor necrosis factors TNF-α-, Interleukin IL-1β-, and Interferon IFN-γ inflammatory cytokines [9]. Zarriello, S. et al suggest that Bone marrow mesenchymal stem/stromal cells BM-MSCs containing Tregs are more therapeutically active, because they present an increased stem cell activity after stroke-induced hypoxia [10].…”
mentioning
confidence: 99%